Dietary beta-carotene, vitamin C and E intake and breast cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC). - Nagel, G; Linseisen, J; Gils, v; Peeters, P; Boutron-Ruault, M; Clavel-Chapelon, F; Romieu, I; Tjønneland, A; Olsen, A; Roswall, N; Witt, P; Overvad, K; et al. (2010)
So far, studies on dietary antioxidant intake, including beta-carotene, vitamin C and vitamin E, and breast cancer risk are inconclusive. Thus, we addressed this question in the European Prospective Investigation into Cancer and Nutrition. During a median follow-up time of 8.8 years, 7,502 primary invasive breast cancer cases were identified. Cox proportional hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). All analyses were run stratified by menopausal status at recruitment and, additionally, by smoking status, alcohol intake, use of exogenous hormones and use of dietary supplements. In the multivariate analyses, dietary intake of beta-carotene, vitamin C and E was not associated with breast cancer risk in premenopausal [highest vs. lowest quintile: HR, 1.04 (95% CI, 0.85-1.27), 1.12 (0.92-1.36) and 1.11 (0.84-1.46), respectively] and postmenopausal women [0.93 (0.82-1.04), 0.98 (0.87-1.11) and 0.92 (0.77-1.11), respectively]. However, in postmenopausal women using exogenous hormones, high intake of beta-carotene [highest vs. lowest quintile; HR 0.79 (95% CI, 0.66-0.96), P (trend) 0.06] and vitamin C [0.88 (0.72-1.07), P (trend) 0.05] was associated with reduced breast cancer risk. In addition, dietary beta-carotene was associated with a decreased risk in postmenopausal women with high alcohol intake. Overall, dietary intake of beta-carotene, vitamin C and E was not related to breast cancer risk in neither pre- nor postmenopausal women. However, in subgroups of postmenopausal women, a weak protective effect between beta-carotene and vitamin E from food and breast cancer risk cannot be excluded.